The Role of the Gayo Lues District Government in Handling Road Damage in Umelah Village, Blang Pegayon Subdistrict, Aceh Province - Yunita, Nelly; Akmal , Artha Dini (The Future of Education Journal, 2025)
This study aims to determine the role of the Gayo Lues Regency Government in handling road damage and its impact on community activities in Umelah Village, Blang Pegayon District. The current condition of the roads in Umelah Village is very concerning because they are potholed, gravelly, and slippery when it rains, thereby hampering community activities in the economic, educational, and public service sectors. This study uses Michael Todaro's (1998) theory, which explains the role of government in infrastructure development, including the provision of facilities and infrastructure, improving community efficiency and productivity, public accessibility, and coordination and resource management. Based on interviews with the Public Works Office, the Blang Pegayon Sub-District Head, the Umelah Village Head, KUA (Office of Religious Affairs) employees, and the community, it was found that the government has taken initial steps such as surveying and measuring the roads, but repairs have not been carried out due to budget constraints, damaged equipment, and development priority policies. As a result, community activities have been disrupted and their welfare has declined. Greater attention is needed from the government in terms of equitable development so that infrastructure can be enjoyed fairly by the entire community